Enhancer choice in cis and in trans in Drosophila melanogaster: Role of the promoter. - Morris, J.R.; Petrov, D.A.; Lee, A.M.; Wu, C. (Genetics, 2004)
Eukaryotic enhancers act over very long distances, yet still show remarkable specificity for their own promoter. To better understand mechanisms underlying this enhancer-promoter specificity, we used transvection to analyze enhancer choice between two promoters, one located in cis to the enhancer and the other in trans to the enhancer, at the yellow gene of Drosophila melanogaster. Previously, we demonstrated that enhancers at yellow prefer to act on the cis-linked promoter, but that mutation of core promoter elements in the cis-linked promoter releases enhancers to act in trans. Here, we address the mechanism by which these elements affect enhancer choice. We consider and explicitly test three models that are based on promoter competency, promoter pairing, and promoter identity. Through targeted gene replacement of the endogenous yellow gene, we show that competency of the cis-linked promoter is a key parameter in the cis-trans choice of an enhancer. In fact, complete replacement of the yellow promoter with both TATA-containing and TATA-less heterologous promoters maintains enhancer action in cis.